Causality between Ankylosing Spondylitis and osteoarthritis in European ancestry: a bidirectional Mendelian randomization study - Lu, Yangguang; Lu, Di; Zhang, Hongzhi; Li, Haoyang; Yu, Bohuai; Zhang, Yige; Hu, Hantao; Sheng, Hongfeng (Frontiers in Immunology, 2024)
Objective: To explore the bidirectional causal relationship between Ankylosing Spondylitis (AS) and Osteoarthritis (OA) at the genetic level within the European ancestry.Methods: We implemented a series of quality control steps to select instrumental variables (IVs) related to the exposure. We conducted two-sample Mendelian randomization (MR) using the inversevariance weighted method as the primary approach. We adjusted significance levels using Bonferroni correction, assessed heterogeneity using Cochrane's Q test. Sensitivity analysis was conducted through leave-one-out method. Additionally, external datasets and relaxed IV selection criteria were employed, and multivariate MR analyses were performed for validation purposes. Finally, Bayesian colocalization (COLOC) analysis identified common genes, validating the MR results.Results: The investigation focused on the correlation between OA and AS in knee, hip, and hand joints. MR results revealed that individuals with AS exhibit a decreased risk of knee OA (OR = 0.9882, 95% CI: 0.9804-0.9962) but no significant increase in the risk of hip OA (OR = 0.9901, 95% CI: 0.9786-1.0018). Conversely, AS emerged as a risk factor for hand OA (OR = 1.0026, 95% CI: 1.0015-1.0036). In reverse-direction MR analysis, OA did not significantly influence the occurrence of AS. Importantly, minimal heterogeneity was observed in our MR analysis results (p > 0.05), and the robustness of these findings was confirmed through sensitivity analysis and multivariate MR analysis. COLOC analysis identified four colocalized variants for AS and hand OA (rs74707996, rs75240935, rs181468789, and rs748670681).In European population, individuals with AS have a relatively lower risk of knee OA, whereas AS serves as a risk factor for hand OA. However, no significant causal relationship was found between AS and hip OA. Additionally, it offers novel insights into genetic research on AS and OA.